Antiaging Effect of Leaves of Different Extract Salvia Splendens: Antiaging Effect of Leaves of Different Extract Salvia Splendens - Mittal, Abhilasha (International Journal of Pharmaceutical & Biological Archive, 2018)
The objective of the present work is to study the in vitro antioxidant activities of petroleum ether, ethyl acetate, and methanolic extracts of leaves of Salvia splendens. The extracts were studied using 1,1-diphenyl-2-picrylhydrazyl, hydrogen peroxide (H2O2), total phenolic content (TPC), and total flavonoid content (TFC). The TPC and TFC were estimated taking gallic acid and rutin calibration curve, respectively. All the extracts possess in vitro antioxidant activities. However, the order of possessing activities was methanolic > ethyl acetate > petroleum ether extracts of leaves S. splendens. The TPC and TFC were highest in methanolic extract. It can be concluded that the extract of the leaves of S. splendens, possess antioxidant activities. The methanolic extract of leaves of S. splendens possesses highest antioxidant activity in-vitro.